FOOD AND FEEDING HABITS OF THE HORSE-MACKEREL, CARANX KALLA (CUV. & VAL.) - Kagwade, V N (Indian Journal of Fisheries, 2011)
The importance of the knowledge of food and feeding habits of a fish in understanding its fishery biology has been very well established. Often it helps in finding out the seasonal variations in the distribution of a fish species. Sometimes the rate of feeding has a bearing on the spawning of the fish. The nature of the food composition of a fish will also throw light on the possible habitats it frequents. Chidambaram and Venkataraman (1946), Chacko and Mathew (1955) and Kagwade (1965) have given short accounts of the food of Caranx kalla. The food and feeding habits of the different species of the horse-mackerel have been described briefly in the works of Datar (1954), Kuthalingam (1955, ’59) and Tandon (1960). But for these, there is no other published account on the food and feeding habits of C. kalla which forms an important component of the fish catches both on the east and west coasts of India. Hence, an attempt has been made here to study this aspect in detail.